Beyond The Red Eye: Rational Clinical Management And Antibiotic Stewardship In Pediatric Acute Bacterial Conjunctivitis At Primary Care Level - Lalu Hermawan Ranova (Universitas Pahlawan Tuanku Tambusai, 2026)
Acute bacterial conjunctivitis is one of the most common ocular conditions encountered in pediatric primary healthcare services. The disease is characterized by inflammation of the conjunctiva caused by bacterial infection and may lead to discomfort, temporary visual disturbance, and increased transmission risk among household contacts and school-aged children. Although many cases are self-limiting, prompt diagnosis and appropriate management remain important to accelerate clinical recovery and reduce unnecessary antibiotic exposure. This paper aims to discuss the clinical presentation, diagnosis, management, and follow-up outcomes of pediatric acute bacterial conjunctivitis in a community health center while emphasizing the importance of antibiotic stewardship in primary care practice. Clinically, bacterial conjunctivitis commonly presents with conjunctival hyperemia, mucopurulent discharge, eyelid sticking upon waking, and mild ocular irritation. Diagnosis is primarily established through history taking and ophthalmologic examination, including visual acuity assessment and anterior segment evaluation to exclude corneal involvement or other serious ocular conditions. Management includes topical antibiotic therapy, hygiene education, and monitoring for clinical improvement. In this case, significant improvement was observed after treatment, demonstrated by resolution of conjunctival injection and disappearance of ocular discharge during follow-up evaluation. Early clinical recognition and rational antibiotic use are essential to optimize patient outcomes while minimizing antimicrobial resistance in primary healthcare settings.